To Begin With- - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses the importance of surface preparation for home painting projects and home maintenance. Provides tips for completing home "paintenance" such as repairing wall cracks, hiring a professional, and inspecting the roof. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Dwellings--Maintenance and repair; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint